WATER LEVEL MONITORING SYSTEM IN WATER UTILITY COMPANY OPEN CHANNELS BASED ON INTERNET OF THINGS - Danti, Trisna Elma; Abdullah, Bualkar; Arifin, A (Universitas Mataram, 2022)
Monitoring the water level in the open channels of the regional water utility company needs to be carried out to ensure the availability of raw water to be processed. This research focuses on making a prototype of a water level monitoring system in an open channel utilizing the WSN (Wireless Sensor Network) component as an application of the IoT (Internet of Things) concept. Monitoring the water level in the open channel is carried out using the infrared sensor GP2Y0A02KF0Y. The real-time measurement results are then sent using XBee wireless communication, then processed by the Raspberry Pi to be saved to a database and displayed on the website. The measurement data can be presented on the website in graphs and tables. The GP2Y0A02YK0F sensor has a measurement error of 1.02% with a correlation coefficient of 0.9998. The average delay in sending data to the website is 1 second. The monitoring system can work well when measuring the water level in an open channel. The advantages of this research are that the instrument used has a high level of accuracy at an affordable price, uses low power, is easy to operate, and can store and present real-time data